The use of nanoindentation for determining internal lengths and the constitutive response of monument materials: models and experiments - Konstantinidis Avraam A.; Frantziskonis George; Askes Harm; Aifantis Elias C. (Journal of the Mechanical Behavior of Materials, 2016)
An alternative interpretation of nanoindentation experimental data and the associated phenomenon of indentation size effect (ISE) is proposed on the basis of a simple gradient elasticity equation, used to account for the development of elastic gradients generated by the geometry characterizing the indenter-specimen system. An application is considered for marble, i.e. a construction/restoration material.